Quantification of 5-FU in skin samples for the development of new delivery systems for topical cancer treatment - Petrilli, R.; Eloy, J. O. [UNESP]; Paschoal, J. A.R.; Lopez, R. F.V. (My University, 2018)
5-Fluorouracil (5-FU) is used for the topical treatment of pre-cancerous skin lesions. However, previous reports focus on 5-FU quantification in plasma samples, failing to provide information about drug quantification in the skin. Therefore, the aim of this work was to develop a simple and reliable analytical method employing HPLC-UV for 5-FU quantification in skin samples. Chromatographic separation was obtained using the commonly available Lichrospher RP-C18 endcapped column. Porcine ear skin matrix-based analytical curves with thymine, as internal standard, were used. 5-FU was eluted at 5.2 min and thymine at 13.0 min. The method was selective, precise and accurate in the linear range from 0.3 to 6 μg/mL. The samples were stable after three cycles of freeze/thawing and extraction efficiency rates above 95% were obtained. In vitro skin penetration studies of an aqueous solution and a commercial cream of 5-FU were performed. The cream improved 5-FU retention into the skin and permeation through the skin compared to the solution. Therefore, the method developed herein can be applied to the study of formulations for topical delivery of 5-FU.